Glutamate and GABA as rapid effectors of hypothalamic “peptidergic” neurons - Schöne, Cornelia; Burdakov, Denis (Frontiers in Behavioral Neuroscience, 2012)
Vital hypothalamic neurons regulating hunger, wakefulness, reward-seeking, and body weight are often defined by unique expression of hypothalamus-specific neuropeptides. Gene-ablation studies show that some of these peptides, notably orexin/hypocretin (hcrt/orx), are themselves critical for stable states of consciousness and metabolic health. However, neuron-ablation studies often reveal more severe phenotypes, suggesting key roles for co-expressed transmitters. Indeed, most hypothalamic neurons, including hcrt/orx cells, contain fast transmitters glutamate and GABA, as well as several neuropeptides. What are the roles and relations between different transmitters expressed by the same neuron? Here, we consider signaling codes for releasing different transmitters in relation to transmitter and receptor diversity in behaviorally-defined, widely-projecting “peptidergic” neurons, such as hcrt/orx cells. We then discuss latest optogenetic studies of endogenous transmitter release from defined sets of axons in situ, which suggest that recently-characterized vital peptidergic neurons (e.g. hcrt/orx, proopiomelanocortin , and agouti-related peptide cells), as well as classical modulatory neurons (e.g. dopamine and acetylcholine cells), all use fast transmitters to control their postsynaptic targets. These optogenetic insights are complemented by recent observations of behavioral deficiencies caused by genetic ablation of fast transmission from specific neuropeptidergic and aminergic neurons. Powerful and fast (millisecond-scale) GABAergic and glutamatergic signaling from neurons previously considered to be primarily “modulatory” raises new questions about the roles of slower co-transmitters they co-express.